Implementation of Live Forensic Virtual Router for Network Traffic Comparison - Firmansyah, Firmansyah; Wibisana, Bayu; Purnomo, Hendri (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2023)
An entrepreneur or a service provider in the internet network world, will certainly find clients with different characters. Clients who are not technology blind, especially routers, sometimes want full access to the router, or some clients who ask to add a router to be able to directly access the router in full. Virtual Router allows clients to process their own network, as if the client has a router. Network forensics has the ability to reconstruct events using a system that stores all data traffic activities on the network, so that investigations can be carried out by looking back at events that have occurred and analyzing events that occurred in the past. Wireshark can review data packages in real time. This means that the wireshark application will monitor all incoming and outgoing data packets through a predefined interface and the next will display the results of the data package